Ahmad Sonhadji’s Moderation Interpretation in `Abru al-Aṡīr Based on the Gadamer’s Hermeneutic Perspective - Lubis, Maisy Rezkiani; Syafruddin, Syafruddin; Wendry, Novizal (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This article aims to explore the moderating dimension of Ahmad Sonhadji's interpretation in his Tafsir, 'Abru al-Aṡīr. This work is based on Sonhadji's lecture on Singapore radio. Some scholars claimed that he was an influential commentator, an icon of commentator and social reformer, and a proponent of the principle of moderation in Singapore. This literature research was carried out using qualitative methods and heuristic analysis. The researchers examined Sonhadji's interpretation of popular verses in the study of moderation. The data were classified based on Gadamer's hermeneutic principles. This research revealed that the meaningful sense of Sonhadji's interpretation gave birth to objective moderate principles, such as upholding justice, obeying the leader's rules, not considering one's own religion as the most correct that leads to humiliation of other religions, not being excessive, and understanding religion proportionally.